Homologous Recombination in Clostridioides difficile Mediates Diversification of Cell Surface Features and Transport Systems - Hannah D. Steinberg (American Society for Microbiology, 2020)
ABSTRACT Illness caused by the pathogen Clostridioides difficile is widespread and can range in severity from mild diarrhea to sepsis and death. Strains of C. difficile isolated from human infections exhibit great genetic diversity, leading to the hypothesis that the genetic background of the infecting strain at least partially determines a patient’s clinical course. However, although certain strains of C. difficile have been suggested to be associated with increased severity, strain typing alone has proved insufficient to explain infection severity. The limited explanatory power of strain typing has been hypothesized to be due to genetic variation within strain types, as well as genetic elements shared between strain types. Homologous recombination is an evolutionary mechanism that can result in large genetic differences between two otherwise clonal isolates, and also lead to convergent genotypes in distantly related strains. More than 400 C. difficile genomes were analyzed here to assess the effect of homologous recombination within and between C. difficile clades. Almost three-quarters of single nucleotide variants in the C. difficile phylogeny are predicted to be due to homologous recombination events. Furthermore, recombination events were enriched in genes previously reported to be important to virulence and host-pathogen interactions, such as flagella, cell wall proteins, and sugar transport and metabolism. Thus, by exploring the landscape of homologous recombination in C. difficile, we identified genetic loci whose elevated rates of recombination mediated diversification, making them strong candidates for being mediators of host-pathogen interaction in diverse strains of C. difficile. IMPORTANCE Infections with C. difficile result in up to half a million illnesses and tens of thousands of deaths annually in the United States. The severity of C. difficile illness is dependent on both host and bacterial factors. Studying the evolutionary history of C. difficile pathogens is important for understanding the variation in pathogenicity of these bacteria. This study examines the extent and targets of homologous recombination, a mechanism by which distant strains of bacteria can share genetic material, in hundreds of C. difficile strains and identifies hot spots of realized recombination events. The results of this analysis reveal the importance of homologous recombination in the diversification of genetic loci in C. difficile that are significant in its pathogenicity and host interactions, such as flagellar construction, cell wall proteins, and sugar transport and metabolism.